Orphan disease: Cherubism, optic atrophy, and short stature - Jeevanandham, Balaji; Ramachandran, Rajoo; Dhanapal, Vignesh; Subramanian, Ilanchezhian; Sai, Venkata (Indian Journal of Radiology and Imaging, 2018)
A 12-year-old female presented with complaints of progressive visual impairment in both her eyes. On clinical examination, she was short for her age and her ophthalmoscopic examination revealed bilateral optic atrophy. Computed tomography of the patient revealed multiple expansile lytic lesions of mandible suggesting cherubism. The optic atrophy was confirmed on magnetic resonance imaging, which additionally revealed bilateral retrocerebellar arachnoid cysts. This association of cherubism with optic atrophy and short stature was grouped as orphan disease by National Institutes of Health and only one case was reported in the literature so far.
Keywords: Cherubism; fibrous dysplasia; optic atrophy; short stature